Giant Two‐Photon Absorption in Mixed Halide Perovskite CH3NH3Pb0.75Sn0.25I3 Thin Films and Application to Photodetection at Optical Communication Wavelengths. Issue 3 (27th December 2017) - Xie, Ying; Fan, Jiandong; Liu, Chong; Chi, Shumeng; Wang, Zeyan; Yu, Haohai; Zhang, Huaijin; Mai, Yaohua; Wang, Jiyang
Abstract: Photodetection in the optical communication wavelength band (OCWB) is a key technique for data processing communications. Photodetectors with integrability, ease of fabrication, low cost, and excellent detection properties are favorable for practical applications. Metal halide perovskite thin films have exhibited intriguing optoelectronic properties. However, their relatively wide intrinsic band gaps indicate that direct photodetection in the infrared OCWB seems impossible. Here, for the first time, direct infrared photodetection covering the OCWB with a metal halide perovskite is demonstrated. Associated with an Sn‐component dependent band gap, a CH3 NH3 Pb0.75 Sn0.25 I3 perovskite thin film is fabricated, whose nonlinear two‐photon absorption can expand the optical response up to 1.8 µm. Two‐photon absorption is studied and a very large absorption coefficient of 1.15 cm kW −1 is measured, a value that is respectively 5 and 10 6 times larger than that of CH3 NH3 PbI3 thin films and halide perovskite bulk crystals. Based on this favorable performance, direct photodetection at 1535 nm in the C‐band of the OCWB and at 1064 nm is characterized. The realization of direct infrared photodetection in a metal halide perovskite provides a possible alternative in advanced integrated optoelectronics and electronics. Abstract : For the first time, giant two‐photon absorption in mixed halide perovskite CH3 NH3 Pb0.75 Sn0.25 I3 thin films is reported . Taking advantage of two‐photon absorption, the optical response can be expanded up to 1.8 µm and direct infrared photodetection covering the optical communication wavelength band is realized with halide perovskite as photodetector.